Determinants Of Electric Bike Purchase Decisions In Langsa City: The Role Of Price Perception, Promotion And Brand Image - Zulfa Eliza; Abdul Hamid; Trisna Sundari (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2026)
This study aims to determine the influence of price, promotion and brand image on the purchase decision of electric bicycles in Langsa City. The method used is a quantitative approach. The determination of the sample in this study uses the theory put forward by Gay and Dhiel which totaled 96 respondents. The data collection technique used questionnaires. The data analysis method uses multiple linear regression, classical assumption test, and hypothesis test (t-test, F and R2 test). The results of the t-test research show that price has a significant positive effect on the purchase decision of electric bicycles in Langsa City. This is evidenced by the results of the statistical test obtained a value of (X1) calculated 2.126 > 1.661 with a significance value of 0.036 < 0.05. Promotion has a significant positive effect on the decision to purchase electric bicycles in Langsa City. This is evidenced by the results of the statistical test obtained a value of (X2) of 2.987 > 1.705 with a significance value of 0.006 < 0.05. Brand image has a significant positive effect on the decision to purchase electric bicycles in Langsa City. This is evidenced by the results of the statistical test obtained a value (X3) of 3.793> 1.661 with a significance value of 0.000 < 0.06. Price, promotion and brand image together affect the decision to purchase an electric bicycle in Langsa City. This is evidenced by the results of the test with the F test which obtained a value of Fcal = 170.926 > Ftable of 2.47 with a significance value of F of 0.000 or F < 0.05.